Indianapolis eaudiobook The true story of the worst sea disaster in u.s. naval history and the fifty-year fight to exonerate an innocent man. - Vincent, Lynn (Simon & Schuster Audio, 2018)
NEW YORK TIMES BESTSELLER * "GRIPPING...THIS YARN HAS IT ALL." — USA TODAY * "A WONDERFUL BOOK." — The Christian Science Monitor * "ENTHRALLING." — Kirkus Reviews (starred review) * "A MUST-READ." — Booklist (starred review) A human drama unlike any other—the riveting and definitive full story of the worst sea disaster in United States naval history. Just after midnight on July 30, 1945, the USS Indianapolis is sailing alone in the Philippine Sea when she is sunk by two Japanese torpedoes. For the next five nights and four days, almost three hundred miles from the nearest land, nearly nine hundred men battle injuries, sharks, dehydration, insanity, and eventually each other. Only 316 will survive. For the first time Lynn Vincent and Sara Vladic tell the complete story of the ship, her crew, and their final mission to save one of their own in "a wonderful book...that features grievous mistakes, extraordinary courage, unimaginable horror, and a cover-up...as complete an account of this tragic tale as we are likely to have" ( The Christian Science Monitor ). It begins in 1932, when Indianapolis is christened and continues through World War II, when the ship embarks on her final world-changing mission: delivering the core of the atomic bomb to the Pacific for the strike on Hiroshima. "Simply outstanding... Indianapolis is a must-read...a tour de force of true human drama" ( Booklist , starred review) that goes beyond the men's rescue to chronicle the survivors' fifty-year fight for justice on behalf of their skipper, Captain Charles McVay III, who is wrongly court-martialed for the sinking. "Enthralling...A gripping study of the greatest sea disaster in the history of the US Navy and its aftermath" ( Kirkus Reviews , starred review), Indianapolis stands as both groundbreaking naval history and spellbinding narrative—and brings the ship and her heroic crew back to full, vivid, unforgettable life. "Vincent and Vladic have delivered an account that stands out through its crisp writing and superb research... Indianapolis is sure to hold its own for a long time" ( USA TODAY ).